Pressureless sintering of zirconium diboride with carbon and boron carbide nanopowder. Issue 9 (1st May 2022) - Neuman, Eric W.; Hilmas, Gregory E.; Fahrenholtz, William G.
Abstract: Zirconium diboride ceramics with and without carbon and boron carbide nanopowder additives were prepared by ball milling with ZrB2 grinding media and pressureless sintering. Additions of up to 1 wt% nano-B4 C and 0.5 wt% C were made to the ZrB2 powder. The materials were then sintered between 1800 and 2300 °C for between 90 and 360 min in an Ar/10H2 atmosphere. After sintering at 2200 °C for 90 min, densities ranged from 88.3 to 90.7% for the ZrB2 with 0–1.0% nano-B4 C addition. Carbon additions of 0.5 wt% and nano-B4 C additions from 0 to 1.0 wt% resulted in densities ranging from 90.9 to 91.9% after sintering at 2100 °C for 90 min. Grain size ranged from 16.6 to 21.7 μm for ZrB2 with nano-B4 C content increasing from 0 to 1.0 wt%, sintered at 2200 °C. For the ZrB2 with 0.5 wt% C, increasing the nano-B4 C content from 0 to 1.0 wt% resulted in a decrease in grain size from 25.4 to 18.5 μm. The densities achieved in this study were lower than previous pressureless sintering studies of ZrB2 that used WC-6Co grinding media, presumably due to the absence of WC and Co that can also act as sintering aids.